Kisüzemi tej és tejtermékek előállítását befolyásoló tényezők vizsgálata - Kőműves, Zsolt; Lukács, Balázs (Acta Scientiarum Socialium, 2015)
An Examination of Factors Affecting the Small-Scale Production of Milk and Dairy Products. The paper examines the factors influencing the competitiveness of milk production. It aims at revealing and characterising natural features, physical, biological, social, economic (market-) and human factors by pointing out the most significant differences at the same time. The paper analyses the efficiency of selected family farms in terms of size, quality, technology and carrying capacity. Finally, the most important relationships are presented and the three most important factors influencing production are highlighted on the basis of the results such as soil, nutrition and livestock.